Designing Data Warehouse Model Using Benefit Cost Ratio Analysis Method - Qusyairi, M.; Sudarma, M.; Dharma, A. (Control systems & computers, 2021)
Data warehouse has function to make the spreaded company’s data to be integrated and concise, thereby it helps the executives in analyzing the existing data to obtain a quick and accurate strategic decision. This research has objective to design a data warehouse within the scope of application of the benefit-cost ratio. As a solution to the feasibility of the company's business, the unity of different data enables it to be combined with the results of the company's in-depth analysis. In designing the model, this research succeeded in designing data warehouse with the application of benefit-cost-ratio method which is used to carry out in-depth analysis of financial sector by providing the feasibility and percentage results of the current business. To summarize, the source data that is processed into the process of extracting, transforming, and loading which built by the star schema will affect the quality of generated data for the process of queries. In addition, the results of the data warehouse used for the decision-making process and feasible business strategy. Мета. Це дослідження має на меті створити сховище даних у межах сфери застосування співвідношення вигоди та витрат. Результати. Таким чином, вихідні дані, які обробляються в процесі вилучення, перетворення та завантаження, які побудовані за допомогою зіркової схеми, впливатимуть на якість генерованих даних для процесу запитів. Крім того, результати сховища даних використовуються для процесу ухвалення рішень та реалізації бізнес-стратегії.